Modeling bioenergy agroecosystems for climate change mitigation and vulnerability assessment - Kent, Jeffrey, author; Paustian, Keith, advisor; Ogle, Stephen, committee member; McMaster, Greg, committee member; von Fischer, Joe, committee member (Colorado State University. Libraries, 2017)
Agriculture is a major driver of anthropogenic climate change while also directly bearing its impacts. In addition to emissions related to farm operations and inputs, substantial greenhouse gases are released from cropland soils. These include carbon dioxide (CO2) fluxes due to long-term changes in soil organic carbon pools, and nitrous oxide (N2O) produced by soil microbes primarily from excess nitrogen (N) fertilizer not assimilated by crops. Agricultural bioenergy systems are expected to produce liquid fuels with lower life-cycle emissions than gasoline. Current US policy specifies several emissions reduction tiers for biomass-derived liquid fuels, ranging from 20% lower than gasoline for corn grain ethanol to 60% lower for ethanol made from perennial grasses or agricultural residues. While these tiers are based on detailed life-cycle assessments of "average" production conditions, they fail to convey the potentially large variability in emissions arising from farm management and biophysical factors. The first half of this dissertation uses a survey of management practices from suppliers of corn grain to a biorefinery in the US Midwest to explore the magnitude and sources of this variability. The first phase of that study finds that feedstock from most of the farms would achieve the statutory threshold of 20%, but that best-performing farms may be producing grain that would lead to fuel with 50% lower life-cycle emissions than gasoline. Key management practices identified are tillage intensity, efficient N fertilizer use and application of livestock manure. Crop residues, such as corn stover, can also be converted to ethanol. The second part of this study explore the sustainability of corn stover collection for ethanol production by a hypothetical dual-feedstock biorefinery. Stover collection presents a tradeoff: when used to produce ethanol, it displaces emissions from gasoline, but at the cost of less soil organic carbon (SOC) accumulation. Still, soils on these farms could sustain relatively high stover collection rates without net SOC losses or erosion, especially in the context of manure application and reduced tillage intensity. Climate change entails two major phenomena – increasing atmospheric [CO2] and increasing extreme high temperatures – likely to have opposing impacts on agricultural productivity, and these impacts will tend to increase over the course of the 21st Century. Chapter 4 of this work reviews the current understanding of crop responses to elevated atmospheric [CO2] and extreme heat as determined from agronomic studies and analyses of historical climate-yield data. It summarizes consensus findings and presents emerging topics in need of further research, and compares the state of knowledge with the simulation approaches employed by several major crop models. The increasing atmospheric [CO2] that largely drives climate change supports increased rates of photosynthesis in C3 plants and improved water use efficiency in all plant types. The magnitude of this fertilization effect is uncertain, however, and recent free atmospheric CO2 enrichment (FACE) experiments appear to show reduced gains relative to earlier enclosure experiments. Chapter 5 tests the hypothesis that the algorithm designed to simulate the CO2 effect in the DayCent ecosystem model overestimates crop responses to elevated [CO2] as observed under FACE conditions.